Pemberdayaan Siswa SMK Melalui Peningkatan Literasi Digital Dan Pemahaman UU ITE Untuk Mendukung Pendidikan Berkualitas (Sdgs 4) - Wina Puspita Sari; Muria Putriana; Indah Fajar Rosalina; Qoryna Noer Seyma El Farabi; Kayla Sulendra Kusumah; Muhammad Ardi Himawan; Muhammad Faishal Alghoniyyu; Najwa Aulia Khansa (CV. ITTC INDONESIA, 2025)
Abstract This community service activity aims to empower vocational school students through increasing digital literacy and understanding of the Electronic Information and Transaction Law (ITE Law) in order to support the achievement of the 4th point of the Sustainable Development Goals (SDGs), namely quality education. Based on a series of activities that include pre-activities, educational interventions, and post-activity evaluations, it was found that the level of digital literacy of SMK Negeri 33 North Jakarta students is very enthusiastic but there are several points to be concerned about, namely the obstacles to the majority of students not understanding the importance of digital literacy, including the ability to verify information, digital ethics, and legal consequences in cyberspace. Understanding of the ITE Law, including its revisions, important articles, legal sanctions, and personal data protection, is also still limited. The educational interventions carried out succeeded in increasing students' awareness, but the post-test results showed that their comprehension had not improved significantly, with the average comprehension score only ranging from 23%–26%. This is likely influenced by the difference in difficulty between pre-test and post-test questions, as well as the limited implementation time. Therefore, a more intensive, contextual, and sustainable advanced educational strategy is needed so that students not only understand the technical aspects of digital literacy, but also be able to apply it ethically and legally in their daily lives.Keywords: digital literacy, ITE Law, student empowerment, vocational schools, quality education, SDGs 4